INVESTIGATION INTO KNOWLEDGE OF NON-CARIOUS CERVICAL LESIONS AMONGST ROMANIAN DENTAL PRACTITIONERS - STATISTICAL STUDY - Andreea Stănuşi; Veronica Mercuţ; Mihaela Ionescu; Sanda Mihaela Popescu; Monica Scrieciu; Adrian Stefan Stănuşi; Ioana Mitruţ; Răzvan Eugen Ghiţă; Adina Turcu; Cristiana Petcu (Romanian Society of Oral Rehabilitation, 2020)
Aim of the study This study investigated the knowledge amongst dentists and senior dental students from Romania, regarding the clinical forms of tooth wear, its etiology and various treatment options for non-carious cervical lesions. Material and methods A questionnaire was sent electronically to Romanian dentists and dental students using social media. The survey had 16 questions regarding the prevalence of non-carious cervical lesions in the participants dental practice, the awareness of their clinical signs, etiological mechanisms and treatment options. Results Romanian dentists and dental students felt competent in diagnosing and treating tooth wear and non-carious cervical lesions, although the awareness of their etiology was moderate. For the restoration of non-carious cervical lesions, the material preferred by Romanian dentists and dental students was flowable composite. Conclusions Our study showed the need for further clinical and laboratory studies of the etiological mechanisms of tooth wear and non-carious cervical lesions for a better understanding amongst dental practitioners.